Indigenous knowledge: Logging the forest - Tropical Forest Trust (Technical Centre for Agricultural and Rural Cooperation, 2008)
The Mbendjele Pygmy communities of northern Republic of Congo work together with an international logging company to help protect the forest. With GPS and a new radio station, the indigenous people keep the company and the community informed